Caracterização geológica, petrográfica e geoquímica de Granitos Arqueanos da Folha Marajoara, Terreno Granito-Greenstone de Rio Maria Sudeste do Pará - DIAS, Samantha Barriga (Universidade Federal do Pará, 2022)
During geological mapping in the Marajoara Sheet, located in the south portion of Rio Maria Granite-greenstone Terrane, southeastern of Amazonian Craton, three groups of Archean granites were distinguished: The Guarantã Suite, the Rancho de Deus Granite and Leucogranitic stocks. The first group is composed of three plutons, named Guarantã Granite (Gg), Azulona Granodiorite (GDaz) and Trairão Granodiorite (GDt), which are intrusive in the Arco Verde Tonalite and were assembled in the Guarantã Suite. The Rancho de Deus Granite is an oval stock, in contact with the Rio Maria Granodiorite and the Guarantã Granite, the latter contact being controlled by a regional shear zone. The third group is formed by small leucogranite bodies, intrusive in the Arco Verde Tonalite and Rio Maria Granodiorite. The epidote-biotite granodiorites to monzogranites of the Guarantã Suite display EW to NW-SE foliation and a porphyritic texture, with coarse alkali feldspar phenocrysts in a fine- to medium-grained matrix. The Rancho de Deus Granite is composed of hornblende-biotite monzogranites with a discrete foliation and porphyritic texture, displaying coarse alkali feldspar phenocrysts in a medium, even-grained matrix. The leucogranites are equigranular, medium-grained rocks. Geochemical data show that the Guarantã Suite and the leucogranites are dominantly peraluminous rocks, whereas the Rancho de Deus rocks vary from metaluminous to peraluminous granites. The three granite groups show strong geochemical contrasts. The Guarantã Suite is enriched in Al2O3, CaO, Na2O, Ba, Sr and Ga and impoverished in Fe2O3, K2O, MgO, Rb and Th compared to the Rancho de Deus Granite. On the other hand, the leucogranites are enriched in SiO2 and K2O and impoverished in Fe2O3, MgO, Na2O, CaO, P2O5, Ba, Sr, Zr, compared to the other two groups. The three groups exhibit moderate to strong HREE fractionation; the Guarantã Suite granites show only discrete negative or positive europium anomalies or are devoid of it. The europium anomalies in the Rancho de Deus Granite are discrete but always negative and those of the leucogranites are also negative but more important. The Rancho de Deus Granite and the Guarantã Suite rocks are similar geochemically to the Archean CA2 calcalkaline granites. However, the geochemical contrasts between these two groups cannot be explained by magmatic differentiation processes, because their rocks have similar SiO2 contents and display distinct trends in geochemical plots. Hence, the hypothesis of a genetic linking between these two granites is discarded and it is assumed that their magmas derived from different sources or evolved by different magmatic processes or both. A comparison between the three studied granite groups and similar Archean rocks of the RMGGR has shown that the Guarantã Suite rocks are similar to the granodiorites and monzogranites found in small satellite stocks associated with the Xinguara Granite pluton and with the Guarantã Granite, as originally defined by Althoff (1996). The Rancho de Deus Granite is similar to the Rio Maria Granodiorite and other rocks of the sanukitoid series. Finally, the leucogranites display petrographic and geochemical affinity with the Mata Surrão Granite. The large area of exposition and volume of the Guarantã Suite demonstrated that this variety of leucogranites was relevant in the evolution of the RMGGT and that, besides the Xinguara and Mata Surrão potassic calc-alkaline leucogranites, they should be considered as an important event of granitic magmatism in the RMGGT. This suite is better exposed in the Marajoara area, but similar rocks, alike those of the satellite stocks of the Xinguara pluton, were previously described and other similar rocks were probably mixed with the mentioned leucogranites in the past.